Model Integrated dalam Pembelajaran Terpadu di Sekolah Dasar - Sari, Mulia Wulan; Faikoh, Hamda; Latip, Asep Ediana (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
Studying the integrated learning paradigm further is the aim of this research. A literature perspective methodology taken from various journals was used in this research. The integrated model is a unifying learning exercise that integrates several subjects at once in one face-to-face meeting to provide students with meaningful experiences, according to the analysis findings of several journals. The goal of this strategy is to produce a more realistic and contextual learning environment. This article outlines the basic ideas of the Blended Learning Model, lists guiding principles for its implementation, and emphasizes how the model can help students learn more effectively. This article also examines the difficulties that may arise when installing Integrated. By using this strategy, it is believed that a more interesting, innovative and relevant learning environment can be produced.